Peran Ulama dan Baznas Kalimantan Selatan dalam Peningkatan Zakat Produktif di Kalimantan Selatan - Hakim, Budi Rahmat; Ridani, Muhammad Noor; Fatmawati, Amelia; Haris, Muhammad (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
Productive zakat in South Kalimantan is still relatively low. This is caused by several factors, such as the lack of public understanding of productive zakat, the lack of innovative productive zakat programs, and weaknesses in productive zakat management. This research aims to understand the role of Ulama and Baznas South Kalimantan in increasing productive zakat in South Kalimantan. This research uses a qualitative approach with a case study method. The results showed that Ulama and Baznas South Kalimantan have an important role in increasing productive zakat. In the division of tasks, principles, and functions, Ulama plays a role in providing education and socialization about productive zakat to the community, while Baznas plays a role in managing and distributing productive zakat to productive mustahiq. Through the involvement and figure of Ulama (Tuan Guru) in the promotion and invitation to give zakat in Baznas South Kalimantan, is one of the factors that cause the increase in the ratio of zakat collection every year which will be explained in more detail in this paper.